PERAMALAN IPR TAK BERDIMENSI UNTUK SUMUR TERSTIMULASI MENGGUNAKAN MATRIX ACIDIZING PADA RESERVOIR HETEROGEN BERTENAGA PENDORONG GAS TERLARUT - Aditya Pratama, Rezha
Inflow performance relationship (IPR) describes the behavior of a well flow rate as a function of well flowing pressure. IPRis the most important thing to be analyzed when making production optimization . The characteristics of IPR curve depends on the properties of reservoir fluid, reservoir and the skin at the near wellbore zone. Stimulation using Matrix acidizing method cancause the formation of wormhole around the well so that it can increase the permeability around the wellbore that affect on skin reduction. The majority of empirical IPR equations that have been proposed represent the skin with simplicitic skin in their simulation model. In this study, a new simulation model is used to predict the IPR on stimulated wellusing matrix acidizing method. This model describes the skin due to the wormhole by using naturally fracture model approach (dual permeability) at neat wellbore. this study will also make forecasting for future IPR equation as a function of reservoirpressure. The validity of proposed equation will be tested using field data and compared its accuracy with other IPR equation such asVogel2, Klins3, Sukarno4, Wiggins5, and Amelia. The comparison results show that the proposed equation gives a fairly good accuracy.